Price Prediction System of Basic Commodities Using Long Short-Term Memory Method: Analysis and Implementation for Future Projections - Fahrudin, Rifqi; Kusnadi, Kusnadi; Lukita, Chandra (Journal Research of Social Science, Economics, and Management, 2024)
The uncontrollable prices of basic commodities, especially food commodities, have resulted in losses for producers and consumers in the city of Cirebon. To be able to bridge these problems, it is necessary to make the right decisions. A prediction system is one of the elements that can be used to support the right decision-making. Predictions in decision-making are based on existing data at present and in the past so that they can be used to describe conditions in accordance with the objectives achieved. With an accurate price prediction system for staple food commodities, it is hoped that decision-making will be able to decide on good policies from the Cooperative, Small and Medium Enterprises Service for Trade and Industry (DKUKMPP) for the people of Cirebon City. The method used is Long Short-Term Memory (LSTM). The data used for the basic prices of food commodities, namely the last 3 years in 2020 - 2022, are sourced from the official website of the Ministry of Trade's Market Monitoring System and Basic Needs using Google Colab tools.